Vector Control of Asynchronous Motor of Drive Train Using Speed Controller H∞ - Abdelhak Boudallaa; Mohammed Chennani; Driss Belkhayat; Karim Rhofir (Emerging Science Journal, 2022)
This study proposes the speed control of an asynchronous motor (AM) using the Antiwindup design. First, the conventional vector control based on proportional-integral (PI) controllers is developed for a constant speed set point. Then, a driving cycle is based on measurements on the Safi/Rabat motorway in Morocco using a microcontroller equipped with a GPS device. The collected practical speed is used as a speed reference for conventional vector control. The /Antiwindup controller of the direct rotor flow-oriented control is used to improve the performance of conventional vector control and optimize the energy consumption of the drive train. The effectiveness of the proposed control scheme is verified by numerical simulation. The results of the numerical validation of the proposed scheme showed good performance compared to conventional vector control. The speed control systems are analyzed for different operating conditions. These control strategies are simulated in the MATLAB/SIMULINK environment. The simulation results of the improved vector control of the Asynchronous Machine (AM) are used to validate this optimization approach in the dynamic regime, followed by a comparative analysis to evaluate the performance and effectiveness of the proposed approach. A practical model based on a TMS320F28379D embedded board and its reduced voltage inverter (24V) is used to implement the proposed method and verify the simulation results. Doi: 10.28991/ESJ-2022-06-04-012 Full Text: PDF